Transcriptomic Analysis of Listeria monocytogenes in Response to Bile Under Aerobic and Anaerobic Conditions - Chakravarty, Damayanti; Sahukhal, Gyan; Arick, Mark; Davis, Morgan L.; Donaldson, Janet R. (Frontiers in Microbiology, 2021)
Listeria monocytogenes is a gram-positive facultative anaerobic bacterium that causes the foodborne illness listeriosis. The pathogenesis of this bacterium depends on its survival in anaerobic, acidic and bile conditions encountered throughout the gastrointestinal tract. This transcriptomics study was conducted to analyze the differences in transcript levels produced under conditions mimicking the gastrointestinal (GI) tract. Changes in transcript levels were analyzed using RNA isolated from L. monocytogenes strain F2365 at both aerobic and anaerobic conditions, upon exposure to 0% and 1% bile at acidic and neutral pH. Transcripts corresponding to genes responsible for pathogenesis, cell wall associated proteins, DNA repair, transcription factors, and stress responses had variations in levels under the conditions tested. Upon exposure to anaerobiosis in acidic conditions, there were variations in the transcript levels for the virulence factors internalins, listeriolysin O, etc., as well as many histidine sensory kinases. These data indicate that the response to anaerobiosis differentially influences the transcription of several genes related to the survival of L. monocytogenes under acidic and bile conditions. Though further research is needed to decipher the role of oxygen in pathogenesis of L. monocytogenes, these data provide comprehensive information on how this pathogen responds to the GI tract.